Interhemispheric transfer time and concussion in adolescents: A longitudinal study using response time and event-related potential measures - Christensen, Benjamin A.; Clark, Bradley; Muir, Alexandra M.; Allen, Whitney D.; Corbin, Erin M.; Jaggi, Tyshae; Alder, Nathan; Clawson, Ann; Farrer, Thomas J.; Bigler, Erin D.; Larson, Michael J. (Frontiers in Human Neuroscience, 2023)
Concussion in children and adolescents is a public health concern with higher concussion incidence than adults and increased susceptibility to axonal injury. The corpus callosum is a vulnerable location of concussion-related white matter damage that can be associated with short- and long-term effects of concussion. Interhemispheric transfer time (IHTT) of visual information across the corpus callosum can be used as a direct measure of corpus callosum functioning that may be impacted by pediatric concussion with slower IHTT relative to matched controls. Longitudinal studies and studies testing physiological measures of IHTT following concussion in adolescents are lacking. We used the N1 and P1 components of the scalp-recorded brain event-related potential (ERP) to measure IHTT in 20 adolescents (ages 12 – 19 years old) with confirmed concussion and 16 neurologically-healthy control participants within three weeks of concussion (subacute stage) and approximately ten months after injury (longitudinal). Separate 2-group (concussion, control) by 2-time (3-week, 10-month) repeated measures ANOVAs on difference response times and IHTT latencies of the P1 and N1 components showed no significant differences by group (ps ≥ .25) nor by time (ps ≥ .64), with no significant interactions (ps ≥ .15). Results from the current sample suggest that measures of IHTT may not be strongly influenced at three weeks or longitudinally following adolescent concussion using the current IHTT paradigm.